Constantine and Christianity: The formation of church/state relations in the Roman Empire. - Opoku, Francis (Ilorin journal of religious studies, 2015)
The relationship between religion and government can be intricate and dynamic and has often had important consequences for both. This is especially evident in the change that took place in both the Christian Church and the Roman Empire during the reign of the Emperor Constantine (A.D. 312-337). This paper discusses the effects of the events and legislation of that period on both church and state. It will attempt to explain how as a result of Constantine’s policies, the Christian Church and the Roman State each gained control of, and influence over the other. This in turn resulted in a mutual dependency which allowed and maintained control of the people. The essay begins with an introduction to the subject and a description of the circumstances of Constantine’s rise to power. This is followed by a discussion of Constantine’s Christian conversion, the motives behind it, and the implications of those motives. Next, an account of Constantine’s most important pro-Christian legislation is presented, with an analysis of its effects on church and empire. The focus shifts to his policy development in regard to involvement in church affairs, concentrating on the two major church councils of Arles and Nicaea. Finally the long term results of Constantine’s policies are discussed. The gain, loss and exchange of power are analyzed from both church and government perspectives-simple timeline to aid the reader in understanding the progression of the church-state relationship.